Treatment with ginkgo biloba extract protects rats against acute pancreatitis-associated lung injury by modulating alveolar macrophage - Xu, Xiao-Wu; Yang, Xiao-Min; Bai, Yong-Heng; Zhao, Yan-Rong; Shi, Gong-Sheng; Zhang, Jian-Guo; Zheng, Yi-Hu (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Acute pancreatitis (AP) protease release induces lung parenchymal destruction via inflammatory mediators. Ginkgo biloba has been reported to have anti-inflammatory effects. Aim : To evaluate the effect of ginkgo biloba extract on experimental acute pancreatitis-associated lung injury in the rat and to investigate the underlying mechanisms. Material and methods : Acute pancreatitis was induced in rats by injection of 5% sodium taurocholate into the biliary pancreatic duct. Ginkgo biloba extract (GBE) was administered and pancreas and lung injury were assessed by histological examination. Alveolar macrophages were harvested by bronchoalveolar lavage. Specificity fluorescent probe DAF-FM-DA was applied to observe nitric oxide (NO) bioavailability in alveolar macrophage. The expression of tumour necrosis factor α (TNF-α) and macrophage migration inhibitory factor (MIF) protein in alveolar macrophage was studied by ELISA. Results: In sodium taurocholate-induced acute pancreatitis, treatment with GBE significantly protected rats against lung injury associated with pancreatitis in histological sections. Ginkgo biloba extract had a tendency to down-regulate NO bioavailability compared with the AP group, but without statistical significance. Moreover, TNF-α and MIF at protein levels in alveolar macrophage with GBE treatment were decreased compared with the AP group. Conclusions: These results suggest that GBE could effectively protect rats against acute pancreatitis-associated lung injury. The GBE may inhibit excessive activation of alveolar macrophages from acute pancreatitis-associated lung injury through down-regulation of generation of NO, TNF-α and MIF. These findings suggest that ginkgo biloba extract is a suitable candidate as an effective strategy against acute pancreatitis-associated lung injury.